2014
DOI: 10.1111/jdv.12653
|View full text |Cite
|
Sign up to set email alerts
|

Serum YKL‐40 in psoriasis with and without arthritis; correlation with disease activity and high‐resolution power Doppler ultrasonographic joint findings

Abstract: Serum YKL-40 can be used as a new biological marker for angiogenesis and disease activity in psoriasis with or without PsA. High-resolution PDUS is a non-invasive tool for the evaluation of angiogenesis in PsA patients as well as for the detection of early synovial changes in psoriasis patients without arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…However, that study did not evaluate the relationship between serum YKL-40 levels and the severity of arthritis symptoms. Another study evaluated serum levels of YKL-40 in 48 psoriatic patients, including 26 patients with joint involvement [ 20 ]. The authors performed the clinical assessment of the patients with additional tests: Composite Psoriatic Disease Activity Index, total joint score and high-resolution power Doppler ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…However, that study did not evaluate the relationship between serum YKL-40 levels and the severity of arthritis symptoms. Another study evaluated serum levels of YKL-40 in 48 psoriatic patients, including 26 patients with joint involvement [ 20 ]. The authors performed the clinical assessment of the patients with additional tests: Composite Psoriatic Disease Activity Index, total joint score and high-resolution power Doppler ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…These changes are associated with differential circulatory and synovial expression of angiogenic factors, such as vascular endothelial growth factor (VEGF), angiopoietin-2 (Ang2), placental growth factors (PIGF), and stromal derived growth factor-1 (SDF-1), in addition to cytokines and matrix metalloproteinases (MMPs) [1, 610]. Increased expression of these growth factors has been demonstrated in early PsA synovial membrane compared to RA [7, 9, 11], suggesting that mechanisms involved in regulating the distinct vascular morphology in PsA occur at an early stage of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have supported that YKL-40 has a role in the pathogenesis of psoriasis manifested by its up-regulation in serum of psoriatic patients [9][10][11][12]. They concluded that, the increased YKL-40 may point out psoriatic patients with a higher level of systemic inflammation [13], and can be used as a new marker for evaluation of disease severity and progression in psoriasis [14].…”
Section: Discussionmentioning
confidence: 94%